2013
DOI: 10.1145/2534169.2486006
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth study of LTE

Abstract: With lower latency and higher bandwidth than its predecessor 3G networks, the latest cellular technology 4G LTE has been attracting many new users. However, the interactions among applications, network transport protocol, and the radio layer still remain unexplored. In this work, we conduct an in-depth study of these interactions and their impact on performance, using a combination of active and passive measurements. We observed that LTE has significantly shorter state promotion delays and lower RTTs than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The improvements in the radio area network (RAN) have relatively increased the impact of the core network on the end-to-end quality. Huang et al showed that the RAN latency no longer dominates the overall endto-end latency even in LTE networks [20]. The performance requirements for 6G are 100 Gbps -1 Tbps peak data rate and a radio latency of 0.1 ms [1], [17], which are comparable to fixed networks.…”
Section: B 6g Network Architecturementioning
confidence: 99%
“…The improvements in the radio area network (RAN) have relatively increased the impact of the core network on the end-to-end quality. Huang et al showed that the RAN latency no longer dominates the overall endto-end latency even in LTE networks [20]. The performance requirements for 6G are 100 Gbps -1 Tbps peak data rate and a radio latency of 0.1 ms [1], [17], which are comparable to fixed networks.…”
Section: B 6g Network Architecturementioning
confidence: 99%
“…Communication is a crucial bottleneck in federated networks, compounded by concerns about privacy regarding the transmission of raw data, necessitating the need for local data retention on each device. In fact, federated networks can comprise a multitude of devices, such as millions of smartphones, where network communication can be orders of magnitude slower than local computation [37,38]. Therefore, to accommodate data generated by devices within a federated network, it is imperative to develop efficient communication methods that involve sending small messages or model updates iteratively as part of the training process rather than transmitting the entire dataset over the network.…”
Section: Communication Requirementsmentioning
confidence: 99%
“…A lightweight passive tool has been introduced for the identification of present LTE networks flaw ("used bandwidth less than 50 percent of the available bandwidth"). They suggest a remote control mechanism by using a more LTE friendly transport protocol and applications [21]. In [22], LTE-Advanced features have been highlighted to improve the quality of service (QoS) specifically focusing on network capacity delivery in terms of offloading and congestion control.…”
Section: Background and Literature Reviewmentioning
confidence: 99%